Life Cycle Assessment of Sustainable Building Materials in The Nigerian Construction Industry - Unegbu, Hyginus; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Journal of Sustainable Construction, 2025)
This study presents a comprehensive life cycle assessment (LCA) of sustainable building materials in the Nigerian construction industry, focusing on bamboo, recycled steel, and low-carbon concrete. It evaluates the environmental impacts of these materials across their entire life cycles—from raw material extraction to end-of-life disposal. A mixed-methods approach was employed: primary data were collected via interviews and surveys with industry professionals, while secondary data came from credible literature and databases. Results revealed bamboo as the most environmentally friendly, with the lowest impacts on global warming, ozone depletion, eutrophication, and resource depletion. Low-carbon concrete also offered significant environmental advantages, particularly in reducing greenhouse gas emissions. Recycled steel supported circular economy goals but had higher energy demands and emissions due to its intensive recycling process. Key barriers to adoption in Nigeria included high upfront costs, limited local availability, and inadequate regulatory support. The study recommends strengthening regulatory frameworks, offering financial incentives, boosting local production, and promoting awareness through education and training. These findings underscore the potential of sustainable materials to reduce the environmental footprint of construction in Nigeria and offer practical guidance for policymakers, industry stakeholders, and researchers committed to advancing sustainability in the built environment.